Concurrent Polycythemia of Undetermined Etiology and Smouldering Plasma Cell Myeloma. (16th September 2018) - Katerji, Roula; Hudson, Chad A.
Abstract : The combination of polycythemia and plasma cell myeloma occurring concurrently is very rare and few cases have been reported in the literature. Further, the vast majority of these cases are cases of polycythemia vera and myeloma. Here, we present a case of polycythemia of undetermined etiology and myeloma. The patient is a 48-year-old Caucasian male who was originally diagnosed with polycythemia of undetermined etiology. Twelve years later, when a bone marrow biopsy was performed in an attempt to determine the etiology of the polycythemia, findings diagnostic of plasma cell myeloma were discovered. Subsequent serum studies were also consistent with a plasma cell neoplasm, while evaluation for end-organ damage was negative. A battery of genetic and biochemical tests ruled out various congenital polycythemias, leading to a final diagnosis of polycythemia of undetermined etiology and smouldering plasma cell myeloma. This case highlights that while being unusual, polycythemia and plasma cell myeloma can occur concurrently, and, in this report, we discuss both entities and potential mechanisms of the pathophysiology of the concurrent presentation.